Electrical stimulation: a potential alternative to positively impact cerebral health? - Descollonges, Maël; Chaney, Rémi; Garnier, Philippe; Prigent-Tessier, Anne; Brugniaux, Julien V.; Deley, Gaëlle (Frontiers in Physiology, 2024)
An increasing body of evidence confirms the effectiveness of physical exercise (PE) in promoting brain health by preventing age-related cognitive decline and reducing the risk of neurodegenerative diseases. The benefits of PE are attributed to neuroplasticity processes which have been reported to enhance cerebral health. However, moderate to high-intensity PE is necessary to induce these responses and these intensities cannot always be achieved especially by people with physical limitations. As a countermeasure, electrical stimulation (ES) offers several benefits, particularly for improving physical functions, for various neurological diseases. This review aims to provide an overview of key mechanisms that could contribute to the enhancement in brain health in response to ES-induced exercise, including increases in cerebral blood flow, neuronal activity, and humoral pathways. This narrative review also focuses on the effects of ES protocols, applied to both humans and animals, on cognition. Despite a certain paucity of research when compared to the more classical aerobic exercise, it seems that ES could be of interest for improving cerebral health, particularly in people who have difficulty engaging in voluntary exercise.